Metaphors and Models in Legal Theory - Makela, Finn (Les Cahiers de droit, 2011)
In this article, the author argues that metaphors can be used as the basis for creating models in legal theory. Drawing on the literature on metaphor from the philosopy of language, he contends that metaphors are best understood as speech acts that propose a hypothesis of similarity between two separate domains. This kind of domain mapping, he argues, is the same procedure that underlies many scientific models, which allow us to transpose our understanding of well-understood phenomena to other areas of inquiry. He concludes with the assertion that — far from being merely ornamental uses of language or rhetorical devices — metaphors are important methodological tools in both the construction and critique of legal theory.